Geometry Thinking Ability and Self Efficacy in Problem Based Learning Geogebra Assisted with Self Assessment - Widiastuti, Ririn; Kartono, Kartono; Mariani, Scolastika (Universitas Negeri Semarang, 2021)
The application of learning models and the selection of learning assessments affect learning outcomes. Besides that, the use of interactive software can also make it easier for students to understand the concept of geometry. This study aims to explain the quality of mathematics learning and the ability of thinking geometry in terms of students' self-efficacy of learning of problem-based learning models assisted by GeoGebra with self-assessment. The study was conducted with a mixed-method approach. The study population was students of class XI Al-Asror Semarang Vocational School with sample class XI TPTU 1 as an experimental class and XI TPTU 2 as a control class. The results showed that the quality of learning of problem-based learning models assisted by GeoGebra with self-assessment of the ability to think geometry and self-efficacy in class XI Al-Asror Vocational High School Semarang was very good and the ability to think the geometry of students in the high self-efficacy group showed very good categories, self-efficacy was included in the good category, and low self-efficacy included in the good enough category. So of learning model of problem based learning assisted by GeoGebra with self-assessment can improve students' geometry skills and self-efficacy.